TWO MELTING REGIMES DURING PALEOGENE FLOOD BASALT GENERATION IN EAST GREENLAND: COMBINED REE AND PGE MODELLING - Momme P.; Tegner C.; Brooks C.K.; Keays R.R. (My University, 2006)
Previously published platinum group element (PGE) and rare earth element data (REE) from a sample suite of the Palaeogene flood basalts of the East Greenland rifted margin are used to approximate primary magma compositions by numerical models of mantle melting. Both high-Ti and low-Ti basalts are found intercalated in the coastal section "the Sortebre Profile" in central East Greenland, and the apparent lack of mixing between the two series indicates coexistence of two geographically separated melting regions and plumbing systems during continental breakup above the Palaeogene Iceland plume. The lavas show little or no sign of crustal contamination and the limited variation in La/Sm and Cu/Pd ratios can be interpreted to reflect mantle source composition and melting processes. Numerical modelling indicate that the low-Ti series formed by F~20% melting in a columnar melting regime from a slightly depleted upper mantle source with a relatively normal S-content (~180 ppm S). In contrast, the high-Ti series formed by much lower degrees of melting (F~6%) in a spreading-related, triangular melting regime from a relatively S-poor (~100 ppm S) source. The low-Ti suite was S-undersaturated at the stage of melt segregation from a shallow mantle source due to the high degree of melting. In contrast, the high-Ti suite probably formed from a S-poor source where some low degree melt batches were S-saturated at the stage of deep segregation in distal parts of the triangular melting regime. This suite shows a geochemical high pressure garnet-signature and adiabatic decompression could therefore have played a role in keeping the mantle-derived S in solution before Fe-enrichment related to fractional crystallisation also increased the S-capacity of these melts. © Springer-Verlag 2005.
Keywords: Кайнозой::Палеоген; Cenozoic::Paleogene